Modelo multi-escala para análise estrutural de compósitos viscoelásticos suscetíveis ao dano - Souza, Flávio Vasconcelos de (2013)
Composite materials are increasingly used in many engineering applications. The main advantage of composite materials lies on the possibility to control the individual components and their spatial distributions in order to optimize the performance of the resulting material. Concrete and the asphalt mixtures are some examples of composite materials commonly used in civil engineering. Composite materials commonly exhibit a particular global constitutive behavior due to the different geometries and constitutive behaviors of its individual constituents. Thus, in order to understand and predict the behavior of composite materials in service, it is important to consider the individual behavior of its constituents and their interactions. In this research work, a two scale computational model is developed to predict the mechanical behavior of sand asphalt mixtures, wherein the behavior of the assumed homogeneous larger scale (macro scale or global scale) is determined based on the behavior of the heterogeneous smaller scale (microscale or local scale). The microstructure (local scale) is formed by elastic granite aggregate randomly distributed in a viscoelastic asphalt matrix (asphalt binder mixed with fine aggregates). In the model developed herein, the global scale damage is a result of the formation and growth of cracks and the accumulation of permanent deformations in the local scale. The Finite Element Method is used in order to calculate stresses, strains and displacements and to model the formation and growth of cracks.